Speech by Brigedier General Dato' Prof. Dr. Kamarudin Hussin Vice Chancellor, Dinner with the Cultural Delegate from Uzbekistan - Kamarudin, Hussin, Brig. Gen. Dato’ Prof. Dr. (Universiti Malaysia Perlis, 2010)
Event was held at Putra Palace, Kangar, Perlis.